FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN LAYANAN MOBILE BANKING - Hadi, Syamsul; Novi, Novi (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2015)
This research objectives is to know the influence of the ease of use, benefits, risks, security and the ease of access to the use of mobile banking. This research took 249 respondents of 265 questionnaires received. Respondents taken by accidental sampling, and analyzed using multiple regression of SPSS 17. This research showed that easiness of operation and usefulness are not significant. Risk, easiness of access and security are significant.